Platelet-Derived Growth Factor has Context-Dependent Effects on Osteogenesis in Bone Marrow-Derived Cells - Nicholas Huffman; Julianne Gillis MD; Amogh Magesh; Sreedhara Sangadala MSc, PhD; Jay M. Patel PhD; Jason T. Bariteau MD (Foot & Ankle Orthopaedics)
Category: Basic Sciences/Biologics; Ankle Arthritis Introduction/Purpose: Arthrodesis stands as the primary method for treating advanced osteoarthritis in the foot and ankle [1]. However, a significant hurdle in this procedure is non-union occurrence, emphasizing the need for adjuncts to enhance osteogenesis and ensure successful fusion. Platelet-Derived Growth Factor (PDGF) emerges as the only clinically approved bone graft substitute for ankle and hindfoot fusion. Bone marrow stimulation, crucial for recruiting cells to aid healing in arthrodesis, is a standard step in all fusions. While preclinical studies on PDGF have mainly focused on human cell lines, the in vitro impact of PDGF on marrow-derived cells, crucial for arthrodesis sites, remains unexplored. This study aims to assess the osteogenic potential of PDGF on heterogeneous marrow-derived cells in both 2D and 3D environments. Methods: Marrow-derived cells (MDCs) from young bovine femoral condyle were utilized without sorting or filtering, to maintain heterogeneity. For 2D assays, MDCs were plated at 10,000 cells per well and cultured in osteogenic media. Both alizarin staining and alkaline phosphatase activity were assessed at 14 days. For 3D assays, we cultured MDCs in fibrin gels at 2M/mL. in osteogenic media for 28 days. For 3D analysis, micro CT and alizarin red staining were performed on fibrin gels. Results: In 2D in vitro analysis, PDGF demonstrated significant increase in alizarin red staining and ALP activity [Figure 1A, 1B]. In 3D analysis, PDGF showed no significant increase in and has trended toward a decrease in alizarin red staining and in micro CT [Figure 1C, 1D]. Conclusion: While many studies have examined the impact of PDGF on human cell lines, this is the first work to analyze the effects of PDGF in a representative distal extremity fusion environment. In our current study, in 2D PDGF demonstrates significant osteoinducton, while in 3D, no increase is seen and a trend towards decreased osteogenic function was observed. Our findings reveal that the differential effects of PDGF in 2D and 3D which may vary depending on the surrounding environment. This work highlights the need for further studies to fully grasp how PDGF functions in an arthrodesis.